John the Baptist and Fasting - Olcese, Gianluca (Vox Patrum, 2023)
The Gospels passages describe John the Baptist’s ascetic behaviour in the Judean desert, eating locusts and wild honey, wearing garments made of camel hair. The food choices of St. John are analysed in comparison with the practice of nazirite, and also on the light of Eastern tradition, mostly spread in Syriac Christianity, which interpretation differs, underlining a particular form of ascetism completely characterised by vegetables. Commentaries, mostly dating back to the 4th and 5th centuries, explain the word ‘akrides’ as a particular vegetable. Furthermore, the celebration of St. John’s Eve, as a result of medieval western development, is nowadays characterized by abundance of food, in contrast, with the Gospel description of the life of the Baptist, are compared with the tradition of charivari, known since the Middle Ages.